Model Coaching Supported by LMS in E-Module Development: A Systematic Literature Review on Enhancing Teacher Competence - Ni Nengah Sri Swathi Nengah; A.Wahab Jupri; AA Sukarso; I Putu Artayasa; Joni Rokhmat; Rangga Alif Faresta (Postgraduate Program, University of Mataram, 2024)
This study explores the integration of Learning Management Systems (LMS) with coaching models to enhance teacher competencies, particularly in e-module development. Using the PRISMA framework, the systematic literature review synthesizes global research from 2019 to 2024. The findings emphasize the transformative impact of LMS-supported coaching in professional development, highlighting themes such as digital competency enhancement, collaborative learning, and adaptability in remote education. Significant contributions emerge from regions like are noted in regions such as the United States, the United Kingdom, and Indonesia, alongside persistent challenges including technological disparities, cultural resistance, and infrastructural limitations. The study identifies emerging technologies, including artificial intelligence and adaptive LMS, as promising solutions for advancing teacher training. These insights underscore the need for inclusive, scalable strategies to address global educational challenges and improve teacher professional development frameworks strengthen frameworks for teacher professional development.